(untitled) (International journal of artificial intelligence, 2026)
This article examines the fundamental economic concepts of demand and supply curves and their role in determining market equilibrium. Demand and supply are the core forces that shape price formation and resource allocation in market economies. Understanding how these forces interact is essential for economists, policymakers, and business practitioners. The study explores theoretical foundations, graphical interpretations, and real-world applications of demand and supply mechanisms. The research highlights how consumer preferences, income levels, production costs, technological progress, and government policies influence market behavior. By analyzing equilibrium conditions, the study explains how prices adjust to balance quantity demanded and quantity supplied. Special attention is given to situations where markets experience shortages or surpluses and how these imbalances are corrected through price mechanisms. Furthermore, the article discusses the dynamic nature of market equilibrium in response to external shocks such as inflation, taxation, subsidies, and global economic changes. The research methodology is based on qualitative and quantitative analysis of economic models, statistical data, and academic literature. The findings demonstrate that stable market equilibrium contributes to efficient resource distribution and economic growth. The study also emphasizes the relevance of demand and supply analysis in developing economies, where market imperfections and regulatory interventions are common. By providing a comprehensive overview, this article aims to enhance understanding of market processes and support informed decision-making in economic planning and business strategy.